2019
DOI: 10.17265/2162-5263/2019.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The Cattle Grooming Behavior and Some Problems with Technological Grooming Instruments for Cow Welfare

Abstract: Thanks to grooming in cattle, dirt, dust and parasites that are removed, skin blood circulation is increased and muscles are massaged. However, grooming should be done with appropriate tools and equipment. Otherwise, it can be more damaging than benefit. There would be a risk that can hurt the animal's life if not paid attention, and may result in injury or even tail rupture. Animals exposed to such situations normally want to escape from grooming and show resistance even though they enjoy it very much. Inaccu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Calves used the mechanical brush mainly for grooming their head and neck (71.6% of the visits). It was expected since previous studies in cattle reported that interactions with the brush were focused on the head and neck (36,37). According to Leruste et al (38), cattle scratch themselves on inanimate objects to reach inaccessible parts of the body, such as the head, neck, back, and hindquarters, which is also consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Calves used the mechanical brush mainly for grooming their head and neck (71.6% of the visits). It was expected since previous studies in cattle reported that interactions with the brush were focused on the head and neck (36,37). According to Leruste et al (38), cattle scratch themselves on inanimate objects to reach inaccessible parts of the body, such as the head, neck, back, and hindquarters, which is also consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Meteorological and hydrological data collected up to 2018 provided by the Hydrometeorology Center of An Giang province (Chau Doc station) and the hydrometeorological center of Kien Giang province (Rach Gia station) have been revised, reliable enough, is the basis in calculating the price of agricultural productivity and climate change scenarios in terms of rainfall, temperature, average number of hours of sunshine, humidity, wind speed and other characteristics for this study [13][14][15][16].…”
Section: Data Collection 221 Hydro-meteorology Datamentioning
confidence: 99%